Unveiling the Drivers of Corporate Social Responsibility: The Roles of Profitability, Consumer Proximity, Media Influence, Environmental Awareness, and Tax Aggressiveness - Luh Pande Eka Setiawati; Ni Putu Yuria Mendra (Philippine Social Science Journal, 2025)
To address inconsistent Corporate Social Responsibility (CSR) implementation, this study analyzed the impact of profitability, consumer proximity, media exposure, environmental sensitivity, and tax aggressiveness on disclosures among 99 Indonesian manufacturing firms listed on the IDX from 2022 to 2024. Using multiple linear regression on 297 observations, the analysis reveals that only media exposure and tax aggressiveness significantly drive CSR reporting, suggesting firms utilize disclosures strategically to manage reputation amidst high visibility or aggressive tax planning. Conversely, financial performance and environmental concerns showed no significant influence. These findings underscore the strategic rather than financial motivation behind CSR, offering guidance for corporate decision-making while pointing toward future research on governance structures, broader sectoral comparisons, and digital transformation.